The Role of the Village Head in Community Empowerment Based on Law Number 6 of 2014 in Diversion Village, Keritang District, Indragiri Hilir Regency Fiqih Siyasah Perspective - Madina; Irdamisraini; Yuni Harlina (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
This research is motivated by community empowerment in Pengalihan village, Keritang District, Indragiri Hilir Regency has not been implemented properly, there are still development programs that have not been implemented such as the lack of street lights while the empowerment program that has not been implemented is the mapping of villages and farmer groups that have been formed but have not been properly realized until now. This research also aims to see how the role of village heads and fiqh siyasah reviews on community empowerment. The main problems of writing this thesis are: What is the role of the village head in community empowerment based on Law Number 6 of 2014, how is the Fiqh Siyasah Perspective Review of the role of the village head in the empowerment of the village community of Diversion Village, Keritang District, Indragiri Hilir Regency, and what are the supporting and inhibiting factors of the role of the village head in community empowerment in the village of Diversion, Keritang District, Indragiri Hilir Regency. This research is a qualitative research with a focus on field materials, which is located in Pengalihan village, Keritang District, Indragiri Hilir Regency. The subjects in this study are village heads, village secretaries, hamlet heads and the people of Pengdihan village. The object of this study is the role of the head of the Diversion village. The data in this study used qualitative descriptive analysis. Meanwhile, the data collection used is observation, interviews and documentation analysts. Based on the results of the research, it can be concluded that the head of the Diversion village has carried out his duties and authorities in accordance with Law Number 6 of 2014, but it is less effective in carrying out community empowerment, especially in the field of farmer groups in Baru hamlet of Pengalihan village. If viewed from the review of fiqh siyasah, the head of the Diversion village has carried out his role in accordance with the siyasah dusturiyyah.